Support and Against Historical Cost Accounting: Is it Value Relevance for Decision Making? - Rahmawati, Evi (Universitas Muhammadiyah Yogyakarta, Indonesia, 2006)
This paper reviews the issues on the support and criticism of historical cost accounting (HCA) and the incremental information content on current cost disclosures. Based on literature review this study find that historical cost is still relevant to use in decision making. Empirical studies show evidence both; supporting historical cost accounting and criticisms against the conventional historical cost based financial statements. Issues on historical cost are raised because ofÂ economic condition, inflation, the change in high tech environment, price movements, and regulators statements. Studies shows that historical cost accounting. over the decade: still have power explanatory for investors, which indicates that its benefits outweigh its cost. However, Barth et al. (1996) provide strong evidence on incremental information of current cost disclosures for certain assets and liabilities. This paper concludes that even there are weaknesses (against) HCA, still there are more benefits that we can gain through HCA.